1984
DOI: 10.1007/bf02534716
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the structure of soybean triacylglycerols due to heat

Abstract: Commercially refined soybean oil was heated at 180 C for 50, 70 or 100 hr with aeration. The triacylglycerol fractions separated from the oils by column chromatography on silica gel were fractionated further by silicic acid thin layer chromatography (TLC), and species compositions were determined by argentation TLC and lipase hydrolysis. There was a decrease in the absolute amounts of the triacylglycerols with longer heating periods, such as 21% for 50 hr and 42% for 100 hr. Relatively large changes occurred i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
1

Year Published

1990
1990
2006
2006

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
2
2
1
Order By: Relevance
“…As the number of double bonds increases, the rate of oxidation increases, the ratios of the rates of oxidation of oleate to linoleate to linolenate are reported to be 1:10:20 [27]. The obtained results are in agreement with those obtained by Raghuveer and Hammond [28], by Wada and Koizumi [29], and by Yoshida and Alexander [30] for FA thermal oxidative degradation. These authors reported that the TAGs, with unsaturated FA linked at the sn-2-position of glycerol, are more stable toward thermal oxidation than those with the same acid at the sn-1-or sn-3-position.…”
Section: Effect Of Microwave Roasting On Major Tag Content and Distrisupporting
confidence: 94%
“…As the number of double bonds increases, the rate of oxidation increases, the ratios of the rates of oxidation of oleate to linoleate to linolenate are reported to be 1:10:20 [27]. The obtained results are in agreement with those obtained by Raghuveer and Hammond [28], by Wada and Koizumi [29], and by Yoshida and Alexander [30] for FA thermal oxidative degradation. These authors reported that the TAGs, with unsaturated FA linked at the sn-2-position of glycerol, are more stable toward thermal oxidation than those with the same acid at the sn-1-or sn-3-position.…”
Section: Effect Of Microwave Roasting On Major Tag Content and Distrisupporting
confidence: 94%
“…Raghuveer and Hammond [1] suggested that the TAG having an unsaturated FA linked at the sn-2 position of glycerol were more stable towards autoxidation than those linked at the sn-1 or sn-3 position. These results were in agreement with those of Wada and Koizumi [2] and Yoshida [3]. In contrast, Park and coworkers [4] found no difference in autoxidative activity between randomized and native oil TAG.…”
Section: Introductionsupporting
confidence: 92%
“…It is likely that we did a more complete purification removing all the prooxidants. Although many articles have suggested that the positional change of unsaturated fatty acid in TAG may have some effect on its oxidation (Hoffmann et al, 1973;Wada and Koizumi, 1983;Yoshida and Alexander, 1984;Miyashita and Takagi, 1988;Neff et al, 1992), no difference was shown between natural and randomized com oil TAG in our study. This maybe due to the polyunstaturated nature of com oil TAG, which makes such an effect not significant.…”
Section: Resultscontrasting
confidence: 87%
“…They also proposed that the concentration of unsaturated fatty acid at the sn-2 position of glycerol should stabilize a fat toward oxidation. Later studies confirmed the effect of randomization in stabilizing mixtures of trisaturated and unsaturated TAG towards oxidation at 50°C (Wada and Koizumi, 1983) and also the protection of unsaturated fatty acids at the sn-2 position in oxidizing refined soybean oil under high temperature (180°C) treatment (Yoshida and Alexander 1984). However, others showed that there was no preferential oxidation between the src-l(3) and sn-2 positions in trilinolein (Neff et al, 1990).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation